A levels‐of‐approximation approach to seismic design or assessment of beam‐column joints in shear. (18th November 2020) - Fardis, Michael N.
Abstract: Models are proposed for the shear strength of joints, for seismic design or assessment. At first Level‐of‐Approximation, the joint reinforcement and the column axial force are lumped in a single central Tie in the corresponding direction, whose ends are connected through concrete Struts to the two compressed corners of the joint. Concrete strength and Strut widths are independent of strains. At the second Level‐of‐Approximation, any reinforcement is smeared in the volume of the joint and compressive stresses are taken as uniform in a continuous compression field. Concrete strength is taken to decrease with load cycling and increasing transverse tensile strain. As this approach gives zero strength for unreinforced joints without column axial load, a minimum shear strength is added to that from the compression field model. Its magnitude and the reduction in the strength of the compression field with load cycling, as well as the Strut widths for the first Level‐of Approximation, are calibrated using a database of 277 interior and 389 exterior joints tested to shear failure.